2000
DOI: 10.1258/0004563001899537
|View full text |Cite
|
Sign up to set email alerts
|

Plasma apolipoprotein(b) to LDL cholesterol ratio as a marker of small, dense LDL

Abstract: A predominance of small, dense LDL in plasma is predictive of coronary risk' and a hallmark feature of an atherogenic lipoprotein phenotype (ALP).2 The measurement of small, dense LDL (LDL pattern 'B') has traditionally been based on the separation of LDL subclasses by density gradient ultra-centrifugation and gradient gel electrophoresis. However, these techniques are expensive, time consuming and unsuitable for routine applications and the screening of large cohorts. While more rapid procedures are currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The LDL cholesterol/Apo B ratio is a well-accepted surrogate of LDL particle size, with large ratios being associated with large, less atherogenic LDL particles. 22,23 Wakatsuki et al 24 demonstrated that transdermal estrogen administration de- …”
Section: Sanada Et Almentioning
confidence: 99%
“…The LDL cholesterol/Apo B ratio is a well-accepted surrogate of LDL particle size, with large ratios being associated with large, less atherogenic LDL particles. 22,23 Wakatsuki et al 24 demonstrated that transdermal estrogen administration de- …”
Section: Sanada Et Almentioning
confidence: 99%
“…An extension of this approach is the LDL-C:Apo-B ratio, considered a surrogate for LDL particle density and a low value indicating the presence of sdLDL. 12 More recently, a direct automated assay for sdLDL has become available; this is based on well-characterized detergents and enzymes that selectively react with the different lipid fractions. Both the LDL-C:Apo-B ratio and the direct sdLDL assay have the potential to simplify analysis of LDL subfractions, and thus refine cardiovascular risk assessment.…”
Section: Introductionmentioning
confidence: 99%